(X+3)-2X=35+X

Simple and best practice solution for (X+3)-2X=35+X equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (X+3)-2X=35+X equation:


Simplifying
(X + 3) + -2X = 35 + X

Reorder the terms:
(3 + X) + -2X = 35 + X

Remove parenthesis around (3 + X)
3 + X + -2X = 35 + X

Combine like terms: X + -2X = -1X
3 + -1X = 35 + X

Solving
3 + -1X = 35 + X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1X' to each side of the equation.
3 + -1X + -1X = 35 + X + -1X

Combine like terms: -1X + -1X = -2X
3 + -2X = 35 + X + -1X

Combine like terms: X + -1X = 0
3 + -2X = 35 + 0
3 + -2X = 35

Add '-3' to each side of the equation.
3 + -3 + -2X = 35 + -3

Combine like terms: 3 + -3 = 0
0 + -2X = 35 + -3
-2X = 35 + -3

Combine like terms: 35 + -3 = 32
-2X = 32

Divide each side by '-2'.
X = -16

Simplifying
X = -16

See similar equations:

| 16(x+2)-4x=4(3x+2)-9 | | 8x+66=3x+31 | | x+46=5x+10 | | 89=1x+100 | | 24-9=5x | | 3/4(x-2)=-6 | | 10.44x=26.3 | | 5x(5+4)= | | CosX=-.08092 | | 7x+41=2x+11 | | 2x-4+3x=9 | | 63=5x+23 | | -3(3x+3)-2(1-14x)=3(6+6x) | | CosX=-.089092 | | 2x+17=-3-(-7x) | | 3/4(x-9)=-62 | | p-24=43 | | 5(z-3)=17.5 | | 180=24x-.4x^2 | | x+0.5y=0 | | -3/4(1/4) | | -3/4(1/5 | | (x+6)+(2-x)=16 | | X+(x+1)+(x+3)=41 | | -486=9(10x-5) | | 50x=80(x+-2) | | Tan(2x+36)=tan(5x+60) | | 14(x-2)+3x=42-(x-5) | | x+x=72 | | 4/130÷2 | | n=d/c-s | | 0.1=60000 |

Equations solver categories